2008
DOI: 10.1080/13548500701426729
|View full text |Cite
|
Sign up to set email alerts
|

Acute psychological benefits of aerobic exercise: A field study into the effects of exercise characteristics

Abstract: Eighty volunteers were tested in their natural exercise environment consisting of a fitness centre they regularly attended. Half of the sample exercised on a stationary bicycle, the other half on a treadmill. All participants filled in the Exercise-Induced Feeling Inventory before and after their 20 min of exercise that was performed at self-selected workload. The results revealed that exercise intensity and the other parallel measures like heart rate, perceived exercise intensity and estimates of burned calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 11 publications
1
20
0
4
Order By: Relevance
“…Yet, the second part of the model-pertaining to the intensity of exercise(s)-may be questionable. A number of past investigations have revealed that exercise characteristics have little role in mediating the psychological benefits (Rendi et al, 2008;Szabo, 2003a;Szabo & Á brahám, 2012). Research has also demonstrated that an equal-toexercise duration, low-or no-effort activity, like mindful exercises, music, or humor trigger identical, or greater, changes in affect than exercise (Netz & Lidor, 2003;Szabo, 1988Szabo, , 2003bSzabo, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the second part of the model-pertaining to the intensity of exercise(s)-may be questionable. A number of past investigations have revealed that exercise characteristics have little role in mediating the psychological benefits (Rendi et al, 2008;Szabo, 2003a;Szabo & Á brahám, 2012). Research has also demonstrated that an equal-toexercise duration, low-or no-effort activity, like mindful exercises, music, or humor trigger identical, or greater, changes in affect than exercise (Netz & Lidor, 2003;Szabo, 1988Szabo, , 2003bSzabo, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommend approaches to correcting academic program for sport oriented groups (sport circles' training). Improvement of students' physical fitness has been being regarded by many scientists recent years [3,5,9]. Their works are devoted to physical endurance.…”
mentioning
confidence: 99%
“…The problem of students' physical education improvement has bee being an objects of specialists' attention already for many years [3,21,23]. Analysis of literature sources shows that physical training level, psychic and moral potentials of most students is still rather low [11,22].…”
mentioning
confidence: 99%
“…This reduction may partly explain the moodelevating effects of physical activity. A factor influencing the degree to which aerobic exercise is beneficial appears to be the intensity: low-to moderate-intensity exercise has been shown to be effective in reducing both anxiety and depression, [20] whereas high-intensity exercise has been found in some instances to induce the opposite effect and increase levels of anxiety. [21] Furthermore, moderate-intensity exercise may produce more sustained psychological benefits, probably because it is easier to maintain over longer periods of time.…”
Section: Treatment Effects On Quality Of Lifementioning
confidence: 99%